Combination therapy of hTERTR and FAM96A for hepatocellular carcinoma through enhancing apoptosis sensitivity - Wang, Wan-Peng (Exp Ther Med, 2018)
Avoidance of apoptosis induced by anticancer drugs is an essential factor of carcinogenesis and a hallmark of resistance to cancer therapy. Human telomerase reverse transcriptase receptor (hTERTR) is a potential anti-cancer agent for inhibiting tumor growth. Family with sequence similarity 96 member A (FAM96A) is a ubiquitous, conserved protein and possesses apoptosome-activating and pro-apoptotic tumor suppressor potential in hepatocellular carcinoma (HCC). In the present study, hTERTR and FAM96A were identified as efficient anti-cancer agents for activating apoptosomes and reducing tumor growth. The potential tumor suppressor function of combination treatment with hTERTR and FAM96A in HCC was also investigated. hTERTR and FAM96A proteins were expressed by genetic engineering and their anti-cancer function was explored in vitro and in vivo. Effects of hTERTR and FAM96A on improvement of apoptotic sensitivity and inhibition of migration and invasion were examined in cancer cells and in a mouse model. The present results demonstrated that the therapeutic effects of hTERTR and FAM96A were effective for inhibiting tumor growth and inducing apoptosis of HCC cells in H22-bearing nude mice compared with single agent treatment. hTERTR and FAM96A were found to bind with apoptotic protease activating factor 1 and human telomerase reverse transcriptase, which enhanced the apoptosis of tumor cells and apoptosis sensitivity. In addition, hTERTR and FAM96A therapy enhanced cytotoxic effects by cytotoxic T lymphocyte responses, interferon-γ release, T lymphocytes infiltration and apoptosis on tumor cells. Furthermore, hTERTR and FAM96A protein inhibited tumor growth in HCC mice. In conclusion, the present findings suggested that combination therapy with hTERTR and FAM96A may serve as novel tumor suppressor agents.